1,25(OH)2D3 Glicosídeo de origem fitoterápica suplementada em dietas para leitões em fase de creche - Gregory, Cristine Regina (2023)
The aim of this study was to evaluate the effects of 1,25- dihydroxycholecalciferol glucoside supplementation in diets for piglets on the apparent digestibility of nutrients, zootechnical performance, occurrence of diarrhea, blood and immunological profile, physical-chemical composition of organs and bone characteristics. The digestibility trial (Exp. I) involved 30 male piglets, with initial body weight of 23.87 ± 3.32 kg, distributed in a randomized block design based on body weight, with five treatments: -D3= without supplementary source of vitamin D, +D3= 100% vitamin D requirement supplemented by cholecalciferol (1969 IU in the initial phase) without 1,25(OH)2D3 glucoside supplementation, D3+0.5= 100% vitamin D requirement supplemented with cholecalciferol + 0.5 µg 1,25(OH)2D3 glycoside, D3+1.0= 100% vitamin D requirement supplemented with cholecalciferol + 1.0 µg 1,25(OH)2D3 glycoside, and D3+1 ,5= 100% vitamin D requirement supplemented with cholecalciferol + 1.5 µg of 1,25(OH)2D3 glycoside, with six replicates and one animal per cage (experimental unit). In the zootechnical performance (Exp. II), a total of 135 male piglets, commercial strain, weaned at 25 days of age and initial body weight of 8.02 ± 0.53 kg were assigned in a randomized block design, composed of the same treatments mentioned above, with nine repetitions in time and 3 animals per pen. There was an increase in CRDM (mean daily feed intake) (P=0.0315) for treatments +D3, D3+0.5 and D3+1.0, piglets that received treatment D3+1.0 had higher ADG (P=0.0123) and PCF (final body weight) (P=0.0123). There was a reduction in the occurrence of diarrhea in piglets that consumed the D3+1.0 treatment (P=0.0090). In the pre-initial phase II, alkaline phosphatase activity showed an increase in its concentration in piglets fed with the +D3 treatment (P=0.0180), the vitamin D concentration showed a decrease (P= 0.0072) for the treatment – D3. The concentration of leukocytes showed a decrease for the D3+1.0 treatment (P=0.0327) and the concentration of eosinophils showed a reduction (P= 0.0054) for the D3+0.5 treatment. The variables of relative weight of digestive and non-digestive organs, and the pH of the gastrointestinal content showed no effect of the treatments. The percentage of MO (organic matter) and DM (dry matter) in the heart of piglets fed with the D3+1.5 treatment increased (P=0.0073 and P= 0.0025 respectively), and the MO of the liver and of the kidneys showed an increase for -D3 (P-= 0.0001 and P= 0.0023 respectively). Liver DM percentage was higher (P=0.0001) for treatments -D3, +D3 and D3+0.5. The DM of the kidneys and bones was higher for the D3 treatment (P= 0.0010 and P= 0.0001). The percentage of calcium in the heart showed a higher concentration in the piglets that received the +D3 and D3+0.5 treatments (P= 0.0249), while the percentage of calcium in the bones showed an increase in the piglets that received the D3+0,5 treatment. Treatments -D3, +D3 and D3+0.5 showed an increase in liver phosphorus values (P= 0.0232). The percentages of magnesium in the bones increased for treatments D3+1.0 and D3+1.5 (P=0.0026). The bone development and intestinal health variables showed no effect of vitamin D3 and glycoside supplementation.